PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS VISUAL BLOCK PROGRAMMING (VBP) PADA MATA PELAJARAN DASAR-DASAR TEKNIK JARINGAN KOMPUTER DAN TELEKOMUNIKASI DI SMKN 1 BONJOL - Nurfazila Nurfazila; Heri Mulyono; Regina Ade Darman (Universitas Muhammadiyah Tapanuli Selatan, 2023)
This research aims to develop Visual Block Programming (VBP)-based learning media for the Basics of Computer Network and Telecommunications Engineering subjects at SMKN 1 Bonjol, with a focus on Basic Orientation material for Computer Network and Telecommunications Engineering. The research method used is research and development, by applying the ADDIE development model. The research subjects consisted of 35 class This research uses a validity instrument in the form of a questionnaire filled out by 6 validators to measure the validity of the media being developed. This research used 3 media validators and 3 material validators to measure the validity of Visual Block Programming (VBP) based learning media products. The media validity result was 0.78519 in the